Effective depth of strawberry radicular system under different soil covers and water levels - Pires, Regina Célia de Matos; Folegatti, Marcos Vinicius; Passos, Francisco Antonio; Ambrosano, Gláucia Maria Bovi; Minami, Keigo (Pesquisa Agropecuaria Brasileira, 2000)
The present work was carried out in Atibaia, the major site of strawberry production in the state of São Paulo, Brazil. The aim of this work was to evaluate the root effective depth of the strawberry crop under different water levels and soil covers. The experiment was conducted using a factorial scheme 2x2 (soil covers and water levels). As soil covers a clear plastic and a black plastic were used. Irrigation was applied until the soil water potential reached -0.010 and -0.070 MPa, at 10 cm depth. The root samples were collected beside the plants each 10 cm, up to 60 cm depth, using an auger hole with 7 cm of diameter, 159 days after planting, with five replications. The results concerning root length per unit of volume showed that the roots are concentrated in the upper langers. Soil covers and water levels did not influence the root length distribution. For irrigation purposes the effective strawberry root depth is 30 cm.